The National Policy Framework and Strategy on Palliative Care 2017‒2022: What’s in it for Terminally Ill Inmates in South Africa? - Chesné Albertus (Obiter, 2021)
In South Africa many people suffer from serious, incurable health conditions that may render them incapacitated and/or terminally ill. Such persons may inevitably require holistic care such as palliative care. The adoption in 2017 of the National Policy Framework and Strategy on Palliative Care 2017‒2022 (NPFSPC) in line with the Health Assembly Resolution 67.19 “Strengthening of Palliative Care as a Component of Comprehensive Care Throughout the Life Course” thus marked a significant milestone for advocates of palliative care, as well as for persons affected by terminal illness. Despite this positive step towards the fulfilment of the right to access healthcare, terminally ill persons who are inmates in South African correctional centres are not sufficiently protected by the NPFSPC. While the policy may be lauded for its detailed provisions aimed at affording appropriate care to free persons, it makes but a few fleeting references to inmates who are terminally ill – a very vulnerable group, given the often appalling conditions in correctional centres, the limited resources generally available to inmates and the stigma attached to them. It is therefore submitted that palliative care should be available to all inmates diagnosed with a terminal illness from the moment they are diagnosed. This article also analyses the stated purpose of the NPFSPC in relation to correctional settings, as well as the impact of disease on correctional centres, and the importance of fostering partnerships.